1984
DOI: 10.1115/1.3138475
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Unconfined Compression of Articular Cartilage

Abstract: Analytical solutions have been obtained for the internal deformation and fluid-flow fields and the externally observable creep, stress relaxation, and constant strain-rate behaviors which occur during the unconfined compression of a cylindrical specimen of a fluid-filled, porous, elastic solid, such as articular cartilage, between smooth, impermeable plates. Instantaneously, the "biphasic" continuum deforms without change in volume and behaves like an incompressible elastic solid of the same shear modulus. Rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
377
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 490 publications
(402 citation statements)
references
References 0 publications
25
377
0
Order By: Relevance
“…Further, it has been shown that if its boundary conditions are properly selected, a Mandel-type problem with hollow axisymmetric geometry can be used to analyze the compaction of producing reservoirs [Nguyen and Abousleiman, 2009]. Mandel's problem has also been the focus of biomechanical studies such as unconfined compression of articular cartilage [Armstrong et al, 1984] and bone [Cowin and Mehrabadi, 1992].…”
Section: Mandel's Problemmentioning
confidence: 99%
“…Further, it has been shown that if its boundary conditions are properly selected, a Mandel-type problem with hollow axisymmetric geometry can be used to analyze the compaction of producing reservoirs [Nguyen and Abousleiman, 2009]. Mandel's problem has also been the focus of biomechanical studies such as unconfined compression of articular cartilage [Armstrong et al, 1984] and bone [Cowin and Mehrabadi, 1992].…”
Section: Mandel's Problemmentioning
confidence: 99%
“…Only two material constants are needed to characterize the constitutive behaviour of homogeneous, isotropic, linear elastic materials. As a first approximation, one can simply measure the shear modulus (G) of a cartilage specimen ex vivo and specify the Poisson's ratio ( ) to be a number slightly less than or equal to 0.5, the Poisson's ratio of an incompressible material (Armstrong et al 1984;Wong et al 2000). Typically, the dynamic shear modulus of normal bovine cartilage is measured to be ca.…”
Section: Modelsmentioning
confidence: 99%
“…It is reported in the literature that the out-of-plane Poisson's ratio (n 31 ) can be set to zero without compromising the accuracy of the model [29,30]. This is based on the observation that the equilibrium stress in the axial direction is the same in confined and unconfined compression, which implies that the radial stress is zero in confined compression.…”
Section: Analytical Formulationmentioning
confidence: 99%
“…Therefore, the stress response reduces to the analytical solution for purely isotropic biphasic material developed by Armstrong et al [29].…”
Section: Analytical Formulationmentioning
confidence: 99%
See 1 more Smart Citation